Reliability analysis and plans for successive testing : start-up demonstration tests and applications - Balakrishnan, N., 1956-; Koutras, Markos V.; Milienos, Fotios (Academic Press, 2021)
Reliability Analysis and Plans for Successive Testing: Start-up Demonstration Tests and Applications discusses all past and recent developments on start-up demonstration tests in the context of current numerical and illustrative examples to clarify available methods for distribution theorists and applied mathematicians dealing with control problems. Throughout the book, the authors focus on the panorama of open problems and issues of further interest. As contemporary manufacturers face tremendous commercial pressures to assemble works of high reliability, defined as 'the probability of the product performing its role under the stated conditions and over a specified period of time', this book helps address testing issues.